Draft Annual Plan 1989-90 (Sub-Plan) I-Leh II-Kargil III-Gujjar and Bakerwal Jammu and Kashmir Government - Planning Commission (Planning Commission, 1988)
An outlay of Rs. 4590.00 lakhs has been approved for district Leh for implementation of various developmental schemes during the Seventh Five Year Plan. Against the current year’s (1988-89) approved outlay of Rs. 1150.00 lakhs which includes Rs. 20.37 lakhs for upgradation programme the anticipated expenditure ending March, 1988 is likely to be of the order of Rs. 1299.57 lakhs which includes Rs. 20.37 lakhs under upgradation programme. For 1989-90, an outlay of Rs. 1600.49 lakhs is proposed for consideration of the Planning Commission.
Jammu and Kashmir Government, Planning and Development Department